2022
DOI: 10.1002/acn3.51562
|View full text |Cite
|
Sign up to set email alerts
|

Scientific rationale for a higher dose of nusinersen

Abstract: Objective: The long-term favorable safety profile of nusinersen provides an opportunity to consider a higher dose. We report on the relationships between nusinersen cerebrospinal fluid (CSF) exposure, biomarker levels, and clinical efficacy. Methods: The analyses used data from the CS3A and ENDEAR studies of nusinersen in participants with infantile-onset spinal muscular atrophy (SMA). Steady-state CSF trough (C trough ) levels, plasma phosphorylated neurofilament heavy chain (pNF-H) levels, body weight, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A higher dose of nusinersen is being tested in patients with early and late-onset SMA (DEVOTE study). 68 In Part A, all six enrolled participants aged 6.1 to 12.6 years have completed the study. Common adverse events (headache, pain, chills, vomiting, and paresthesia) were considered related to the lumbar puncture procedure, and there were no safety concerns regarding clinical or laboratory parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher dose of nusinersen is being tested in patients with early and late-onset SMA (DEVOTE study). 68 In Part A, all six enrolled participants aged 6.1 to 12.6 years have completed the study. Common adverse events (headache, pain, chills, vomiting, and paresthesia) were considered related to the lumbar puncture procedure, and there were no safety concerns regarding clinical or laboratory parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Most participants showed stabilization or improved motor function. 68 Parts B and C of the DEVOTE are ongoing.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that NF is elevated in SMA-affected infants and young children compared to healthy controls, and it rapidly declines with treatment by nusinersen before stabilizing above normal [ 107 , 113 , 118 , 165 ]. For example, Finkel et al (2022) analyzed data from the CS3A and ENDEAR studies and found that in infants with SMA, lower NF-H levels in CSF were associated with increased nusinersen dosage, which in turn correlated with better treatment outcomes [ 165 ]. Studies that have evaluated the effects of nusinersen treatment on NF levels in SMA-affected adolescents and adults have yielded conflicting results, suggesting a need for further, standardized studies on these populations [ 109 , 111 , 115 , 121 , 147 149 , 166 , 167 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 demonstrates that NfL and pNfH were used as potential pharmacodynamic (response) biomarkers in the majority of studies that examined the utility of molecular biomarkers for monitoring therapeutic response in SMA. In the majority of studies, a decrease in NfL and pNfH levels was observed following treatment with nusinersen [39,[61][62][63][76][77][78][79][80][81], whereas others observed no change in the levels of these biomarkers [45,56,60,[82][83][84] (Table 2).…”
Section: Monitoring Of Therapeutic Response In Sma Using Molecular Bi...mentioning
confidence: 99%